Educative Imperatives in the Teacher Speech of the SMAN 1 Kwanyar Bangkalan - Musaffak; Laksono, Kisyani; Yohanes, Budinuryanta; Suhartono (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
During the learning process in class, the teacher has indirectly given orders to his students that are educational and pragmatic imperatives in their speech. The purpose of this study is to describe the form of educational imperatives in the speech of teachers of SMAN 1 Kwanyar Bangkalan. This research approach is a sociopragmatic approach. This research method is a qualitative research method. This research data uses qualitative data in the form of data transcriptions from documentation results containing educational imperative forms in the form of words and sentences in a speech by a teacher of SMAN 1 Kwanyar Bangkalan. This qualitative data is intended to describe the form of educational imperatives in the speech of teachers of SMAN 1 Kwanyar Bangkalan. The source of this research data was 3 teachers of SMAN 1 Kwanyar Bangkalan and involved 33 students. Data is taken between January-March 2023. This research data collection technique uses documentation techniques, interviews, field notes. Data analysis was performed with Huberman's version of data. This study concluded that the form of educational imperative in the speech of teachers of SMAN 1 Kwanyar Bangkalan was assertive, directive, and expressive. This educational imperative mode is because teacher statements tend to function to state, inform, report, and demand. Next, the educative impertive findings are directive mode because teacher statements tend to function as commanding, instructing, inviting, and suggesting. Educational imperative is expressive mode because teacher statements tend to function mocking, congratulating, praising, and saying thank you. Impertive educative directive mode teacher statements do not function to instruct, plead, require, coerce, borrow, and interrupt. Thus, assertive, declarative, and expressive speech is used for the teaching and learning process that has educational value from each teacher's imperative. The educative imperative of teacher speech provides education to be mutually responsible for their obligations, motivate, remind, value time, measure self-ability, help the incapable, and encourage.